A comparison of the diagnostic accuracy of in vivo and in vitro photostimulable phosphor digital images in the detection of occlusal caries lesions - Kamburoğlu, K (The British Institute of Radiology., 2010)
OBJECTIVES: The purpose of this study was to compare the accuracy of diagnoses of occlusal caries lesions from digital images captured using a photostimulable phosphor (PSP) sensor under in vivo and in vitro conditions and to present useful clinical data regarding the clinical application of the system. METHODS: The study sample comprised 60 mandibular third molars (30 sound and 30 with occlusal caries) requiring extraction. A pre-extraction and post-extraction image of each tooth were acquired using a PSP sensor. A stopwatch was used to record the time required for the clinical procedures. Patient comfort or discomfort during image acquisition was also recorded. Images were evaluated twice by three observers using a five-point scale. Kappa coefficients were calculated to assess intra- and interobserver agreement. Receiver operating characteristic (ROC) curves were used to assess the diagnostic performance of each observer for both in vivo and in vitro images. The t-test was used to compare A(z) values, with a significance level set at 0.05 (α _ 0.05). The time required for clinical imaging procedures in patients who claimed discomfort and in those who did not was compared using the Mann–Whitney U-test. RESULTS: Intraobserver agreement was almost perfect, whereas interobserver agreement was fair to moderate. No statistically significant differences were found in the accuracy of diagnoses of occlusal caries lesions using in vivo and in vitro digital images. The median time needed for image exposure was 1.04 min and the median time needed to complete the image acquisition procedure was 1.45 min. CONCLUSIONS: The diagnosis of accuracy of occlusal caries lesions using in vivo and in vitro digital images yielded similar results.